Estrategia cognitiva y comprensión lectora en estudiantes del cuarto ciclo de educación básica regular de la I.E. 60050 República de Venezuela, Iquitos 2022 - Melendez Olivera, Jessica Juliana (2023)
Objective: The aim of this study was to determine the relation between the cognitive strategy and the reading comprehension levels in the in students of the fourth cycle of elementary school of the educational institution 60050 República de Venezuela, in the year 2022. Materials and methods: It was applied one structured questionnaire and one test to 147 childrens, previous validation for experts. The study was descriptive – relational and the design was not experimental. It was observed the result of the statistic Tb=0,679; with a significance p<0.05). Therefore, it is considered that there is a significant and moderate connection. Conclusion: The cognitive strategy determine to the reading comprehension levels.